Limit Cycles Bifurcating from a Period Annulus in Continuous Piecewise Linear Differential Systems with Three Zones - Silva Lima, Mauricio Firmino; Pessoa, Claudio [UNESP]; Pereira, Weber F. [UNESP] (World Scientific Publ Co Pte Ltd, 2017)
We study a class of planar continuous piecewise linear vector fields with three zones. Using the Poincare map and some techniques for proving the existence of limit cycles for smooth differential systems, we prove that this class admits at least two limit cycles that appear by perturbations of a period annulus. Moreover, we describe the bifurcation of the limit cycles for this class through two examples of two-parameter families of piecewise linear vector fields with three zones.
Keywords: Piecewise linear vector fields; Poincare map; limit cycles; center; focus